A Reappraisal of ShÄ«âa Juristsâ Referring to the Verses of the Holy Qurâan as Evidence for the Ruling on Marriage to People of the Scripture - Ã™Â…Ã˜ÂÃ˜Â¨Ã™ÂˆÃ˜Â¨Ã›ÂŒ, Ã˜Â³Ã›ÂŒÃ˜Â¯ Ã™Â†Ã˜ÂµÃ˜Â±Ã˜Â§Ã™Â„Ã™Â‡ (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
After mentioning different views on marriage of a Muslim man to a Christian or Jewish woman, this article has addressed as to which of these views are correct from the perspective of the Holy Qurâan. To this end, first the verses in which the prohibition of marriage to the women from among the People of the Scripture is referred to are brought up and the denotation of these verses to the subject are examined; and then, the verses contradicting this denotation are examined; and finally it has been summed up that one of the most important points studied is the inclusiveness of the word idolaters in verse 221 of SÅ«rat al-Baqara to the People of the Scripture, as, given this inclusiveness, which according to the explanations mentioned in the text, the outcome of the research is against it, the contradiction of the two verses 221 of SÅ«rat al-Baqara and verse 10 of SÅ«rat al-Mumtaá¸¥ana with the verse 5 of SÅ«rat al-MÄâida has been studied and concluded that the verse 5 of SÅ«rat al-MÄâida has not been abrogated and the generally accepted view on this topic has been critically reviewed in bringing up the issue.